(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
The rapid evolution of digital technologies has profoundly impacted educational practices worldwide, necessitating the integration of advanced visualization and modeling tools into geometry and graphics instruction. This article investigates the role, efficacy, and challenges of implementing software platforms such as GeoGebra, AutoCAD, SketchUp, Blender, MATLAB, and AR/VR applications in teaching geometry and graphics at various educational levels, with a particular focus on Uzbekistan’s ongoing digital transformation and global benchmarks. Drawing on recent international and national studies, as well as the latest statistical data from PISA, TIMSS, and local pilot projects, the research systematically analyzes how digital visualization and modeling foster spatial thinking, creative problem-solving, and engineering competences. The study follows an IMRAD structure, providing a comprehensive literature-based introduction, a robust methodology grounded in comparative and experimental analyses, detailed results encompassing empirical findings from both Uzbek and international contexts, a critical discussion situating local developments within the global discourse, and practical conclusions and recommendations for policymakers, educators, and researchers. The work concludes that while significant advances have been made, addressing technological infrastructure gaps, teacher training, and curriculum modernization remain crucial for maximizing the pedagogical potential of visualization and modeling technologies in geometry education.